A dinâmica caleidoscópica do processo de aprendizagem coloborativa no contexto virtual: um estudo na perspectiva da complexidade/caos - Valdir Silva (2008)
In recent years there has been significant amoung of research guided by completxity and chaos theories in the area of Applied linguistics (Larsen-Freeman, 1997; Paiva, 2005; van Lier, 2004, Lantolf, 2006, Cameron and Deignan, 2006, among others). The ideas of complexity/chaos consider the inter-relation of agents in a complex system is dynamic, non-linear, open, unpredictable, chaotic, sensitive to inicial conditiaons, subject to strange attractors, bifurcative and self-similar (fractals) In other word, it is highly complex. In the light of these theoretical notions, the discussion in this work is centered on the analysis of 1,370 e-mail exchanged among the adult learners of a Virtual Community of Learning (Discussion List) to show that the process of collaboration for learning is a natural property of this community. Thus, collaboration was regarded as a dynamic event that emerges in the interstice between the predictable and unpredictable of the system, propelling it into its future trajectory. In this research, the concept of dynamizer (dinamizador) was developed and implemented as an alternative proposition and (re)signified for the metaphor of the instructional scaffolding (Wood, Brunner Ross, 1976, Cazden; 1979). To investigate the ethos of this virtual community, I adopted as logic of research - in perspective - the methodology of virtual ethnography (Hine, 2000). The analysis demonstrated that the instructional scaffolding, when focused in the light of the complexity/chaos, is an inadequate metaphor, in its evocative power, to represent the complex dynamics that conforms the process of collaborative learning. Moreover, the concept of dynamizer, despite lacking further studies, presented itself as a valid concept to explain not only the abovementioned process in the collective system and interpersonal of Virtual Learning Environment (VLE), but also the intrapessoal system through the Zone of Proximal Development (ZPD). The discussion herein presented aims to serve as a starting point for reflexions regarding collaborative educational processes in virtual environments.